2011
DOI: 10.5937/sjm1102193v
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control and job satisfaction: PSU employees

Abstract: Previous research studies have demonstrated that internal/external locus of control impacts job satisfaction. The present study thus aims to analyze type of locus of control and its relation with job satisfaction. The study will be of great help for organization to understand and know what type of locus of control their employees has and how it has an impact on job satisfaction.The objectives of this study were: 1-To identify the type of Locus of Control (i.e. Internal or External) present in Public Sector Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Another study related to LOC and its influence on employees' job satisfaction in public sector organization was conducted by Vijayashree and Vishalkumar (2011). The objective of the study was to identify the type of LOC in Public Sector Unit (PSU) in Bangalore and to analyze the impact of different type of LOC on job satisfaction of PSU employees.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Another study related to LOC and its influence on employees' job satisfaction in public sector organization was conducted by Vijayashree and Vishalkumar (2011). The objective of the study was to identify the type of LOC in Public Sector Unit (PSU) in Bangalore and to analyze the impact of different type of LOC on job satisfaction of PSU employees.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The growing literature on LOC examines its influence on employee wellbeing and job performance (Ng et al, 2006;Thomas et al, 2006); job satisfaction (Vijayashree and Jagdischchandra, 2011;Gangai et al, 2016). Internal LOC clearly generates a positive relationship with performance (Thomas et al, 2006:107), and is believed to stimulate innovative behaviors among organisational employees (Prattom & Savatsomboon, 2012:1063.…”
Section: Locus Of Control and Job Performancementioning
confidence: 99%
“…Gangai et al's (2016) study examined the association between LOC and job satisfaction among employees and revealed that employee LOC is critical to improved job performance and productivity. Another study conducted by Vijayashree and Jagdischchandra (2011) states that internal/external LOC impacts on job satisfaction. In particular, their study revealed a positive correlation between internal LOC and job satisfaction as well as between external locus of control and job satisfaction.…”
Section: Locus Of Control and Job Performancementioning
confidence: 99%
“…Mullins (1999:815) revealed how a high level of employee commitment could lead to keenness towards the organisation's benefit. The level of commitment within organisations unswervingly affects employees' and is therefore seen as an issue of great significance (Meyer et al, 1993;Siders et al, 2001;Jaramillo et al, 2005;Vijayashree and Jagdischchandra., 2011).…”
Section: Introductionmentioning
confidence: 99%